2016
DOI: 10.1016/j.jff.2016.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Dietary broccoli protects against fatty liver development but not against progression of liver cancer in mice pretreated with diethylnitrosamine

Abstract: Western-style high fat, high sugar diets are associated with non-alcoholic fatty liver disease (NAFLD) and increased liver cancer risk. Sulforaphane from broccoli may protect against these. Previously we initiated broccoli feeding to mice prior to exposure to the hepatocarcinogen diethylnitrosamine (DEN), and saw protection against NAFLD and liver cancer. Here we administered DEN to unweaned mice, initiating broccoli feeding two weeks later, to determine if broccoli protects against cancer progression. Specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…SFN has drawn considerable attention due to its roles in controlling energy balance and metabolism . Previous articles report that sustained treatment of diet‐induced obese mice or rats with SFN lessens the development of fatty liver . In this study, we document that SFN improves mitochondrial function and elevate mitochondrial biogenesis, reducing lipid content in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 53%
“…SFN has drawn considerable attention due to its roles in controlling energy balance and metabolism . Previous articles report that sustained treatment of diet‐induced obese mice or rats with SFN lessens the development of fatty liver . In this study, we document that SFN improves mitochondrial function and elevate mitochondrial biogenesis, reducing lipid content in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 53%
“…A subsequent study from the same group again showed that broccoli attenuated the NAFLD effects of the Western diet (94). However, in the second mouse study, the broccoli did not slow down hepatocarcinogenesis, but mice were induced with diethylnitrosamine at a younger age (2 wk) and before the administration of broccoli and the Western diet (4 wk to 7 mo) (94). Based on these studies, broccoli can attenuate the effects of NAFLD in mouse models, minimizing the risk that they develop liver adenomas, but not necessarily alter the course of hepatocarcinogenesis.…”
mentioning
confidence: 92%
“…In this study, mice were started on a Western diet and 10% broccoli at 5 wk before induction with diethylnitrosamine at 6 wk (93). A subsequent study from the same group again showed that broccoli attenuated the NAFLD effects of the Western diet (94). However, in the second mouse study, the broccoli did not slow down hepatocarcinogenesis, but mice were induced with diethylnitrosamine at a younger age (2 wk) and before the administration of broccoli and the Western diet (4 wk to 7 mo) (94).…”
mentioning
confidence: 98%
“…Previous studies have indicated that SFN has many biological properties, including anti-oxidant, anti-inflammatory, and anti-bacterial effects [11,12]. SFN has been found to act as a tumor suppressor in many different cancers during cancer progression, including oral, breast, liver, colon, and prostate cancers [13][14][15][16]. In addition, it has been demonstrated that SFN has the ability to prevent carcinogen-induced initiation of oral cancer [14].…”
Section: Introductionmentioning
confidence: 99%